Implementation of the Development of Moral Religious Values in Early Childhood Through Modeling Methods - Safitri, Eva (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2022)
The development of children's religious and moral values is the child's ability to behave and behave. The development of moral religious values for children is related to polite behavior, maintaining good speech, adhering to religious teachings in life. The purpose of this study was to analyze the development of moral religious values in early childhood through exemplary methods. This research uses qualitative research with a literature review method. Methods: References in the form of primary articles of approximately 20 articles, 15 national journals with a period of 5 years, and international journals with a term of 7 years that are accredited and reputable. The sample of this research is related to the value of moral religion in children / exemplary methods with journal criteria selected were: 1) an experimental research; 2) respondents are early childhood; 3) the independent variable is an exemplary method and the dependent variable is the development of religious and moral values; 4) the treatment given is exemplary influence / another factor that can increase the development of religious and moral values in early childhood. Results and discussion: the literature review states that the moral religious values of children in this study are exemplary parents and teachers, exemplary is a dominant problem, the development of children's religious and moral values can be influenced by several factors, including deliberate and unintentional role models, use of audio-visual media, storytelling method, VCD media, role-playing, singing method, habituation method, traditional games, IMTAQ center. Conclusion: exemlpary methods can influence children’s development and the development of moral religious values can be developed in a variety of ways.